The influence of trapping agents on the antitumor efficacy of irinotecan liposomes: head-to-head comparison of ammonium sulfate, sulfobutylether-β-cyclodextrin and sucrose octasulfate. (30th November 2018) - Yang, Wenqian; Yang, Zimeng; Fu, Jingru; Guo, Mengran; Sun, Bingjun; Wei, Wei; Liu, Dan; Liu, Hongzhuo
Abstract : Remote loading technology is an outstanding achievement in liposome-based drug delivery systems. Abstract : Remote loading technology is an outstanding achievement in liposome-based drug delivery systems. Compared with conventional passive loading, remote loading technology exhibits unique superiority in terms of high drug loading efficiency, low leakage rate and adequate drug accumulation. In the intra-liposome aqueous phase, the counterion of the trapping agent can control the state of aggregation/crystallization of the drug-counterion salt, and thereby contribute to control the efficiency of remote loading. Herein, irinotecan (CPT-11)-loaded liposomes were developed using three trapping agents: ammonium sulfate (AS), sulfobutylether-β-cyclodextrin (SBE-β-CD) and sucrose octasulfate (SOS). The corresponding formulations were named as AS liposomal CPT-11, TEA-SBE-β-CD liposomal CPT-11 and TEA-SOS liposomal CPT-11, respectively. Cryo-transmission electron micrographs showed that bundles of CPT-11 fibers were gathered inside TEA-SOS liposomal CPT-11. Furthermore, compared with AS liposomal CPT-11 and TEA-SBE-β-CD liposomal CPT-11, TEA-SOS liposomal CPT-11 demonstrated slower drug release, prolonged circulation time and significantly improved antitumor efficiency. To avoid the protection of ONIVYDE®-related patents, a number of other liposomal CPT-11 formulations are under preclinical investigation or even in clinical trials. Our study gives new insights into the impact of the trapping agent on remote loading, and provides valuable information to evaluate the development of CPT-11 loaded liposomes.